2017
DOI: 10.1186/s12993-017-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-enhancing and antioxidant activities of the aqueous extract from Markhamia tomentosa (Benth.) K. Schum. stem bark in a rat model of scopolamine

Abstract: BackgroundPlants of the genus Markhamia have been traditionally used by different tribes in various parts of West African countries, including Cameroun. Markhamia tomentosa (Benth.) K. Schum. (Bignoniaceae) is used as an antimalarial, anti-inflammatory, analgesic, antioxidant and anti-Alzheimer agent. The current study was undertaken in order to investigate its anti-amnesic and antioxidant potential on scopolamine-induced cognitive impairment and to determine its possible mechanism of action.MethodsRats were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…The biochemical results obtained in this study indicated that COT and 6HLN exhibit an antioxidant profile in the SCOP-induced zebrafish model of AD. Several reports showed that SCOP treatment induces oxidative stress in the brain of zebrafish [ 36 , 37 , 38 , 92 , 93 ] or rodents [ 64 , 96 , 97 , 98 , 99 ]. In a cell line derived from Danio rerio gill tissue, NIC treatment (3–7 mg/L for 12 h) has been shown to induce intracellular ROS generation in a dose-dependent manner [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical results obtained in this study indicated that COT and 6HLN exhibit an antioxidant profile in the SCOP-induced zebrafish model of AD. Several reports showed that SCOP treatment induces oxidative stress in the brain of zebrafish [ 36 , 37 , 38 , 92 , 93 ] or rodents [ 64 , 96 , 97 , 98 , 99 ]. In a cell line derived from Danio rerio gill tissue, NIC treatment (3–7 mg/L for 12 h) has been shown to induce intracellular ROS generation in a dose-dependent manner [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we induced memory impairment by administering the muscarinic acetylcholine receptor antagonist scopolamine or nicotinic acetylcholine receptor antagonist mecamylamine to rats. Scopolamine is reported to inhibit cholinergic functions in the central nervous system and increase the activity of acetylcholinesterase (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism was suggested for Markhamia tomentosa extract while exposing scopolamine-treated rats to plant aqueous formulations. 109 In this way, it seems that a major mechanism in scopolamine-induced memory impairment reversal exhibited by the tested plant extract may be linked with oxidative stress decrease in several key brain areas such as hippocampus or brain cortex followed by working memory improvement.…”
Section: Some Molecular Aspects Of Plant Extract Components Relevant mentioning
confidence: 93%